Organometallic gold(I) and gold(III) complexes for lung cancer treatment - Zhang, Juzheng; Li, Yanping; Fang, Ronghao; Wei, Wei; Wang, Yong; Jin, Jiamin; Yang, Feng; Chen, Jian (Frontiers in Pharmacology, 2022)
Metal compounds, especially gold complexes, have recently gained increasing attention as possible lung cancer therapeutics. Some gold complexes display not only excellent activity in cisplatin-sensitive lung cancer but also in cisplatin-resistant lung cancer, revealing promising prospects in the development of novel treatments for lung cancer. This review summarizes examples of anticancer gold(I) and gold(III) complexes for lung cancer treatment, including mechanisms of action and approaches adopted to improve their efficiency. Several excellent examples of gold complexes against lung cancer are highlighted.